PENGARUH VALVE CLEARANCE TERHADAP PERFORMANCE DAN EMISI GAS BUANG PADA MESIN YAMAHA JUPITER Z1 - Fendi Agong Fajari; Abdul Ghofur (Universitas Lambung Mangkurat, 2019)
Vehicle is the most needed tool as a transportation medium. This is due to the human need for vehicles is very important for the community. This study aims to determine the effect of valve clearance on performance and exhaust emissions on yamaha jupiter Z1 engine. In this study the researchers used variations of valve clearance intake and exhaust 0.06 mm up to 0.15 mm with dynotest experimental methods for performance testing and using experimental methods with gas analyzer parameters for exhaust gas emissions testing. From the results of performance tests that have been done got the best power and torque that supports engine performance. The 0.15 mm intake valve clearance variation obtained the best power yield with 93.11% achievement and the power value of 9,180 Hp at 8852 rpm, while for the best torque found on the 0.12 mm intake valve clearance variation obtained with achievement of 92.98% and the torque value is 9,205 Nm at 6136 rpm engine speed. From the exhaust gas emission test results, the valve gap size is sufficient to affect the results of exhaust emissions in a vehicle. Variations of valve clearance that obtained the results are ideal and safe for the environment that is 0.12 mm estrangement on the variation of exhaust and estrangement 0.15 mm on the variation of intake that has low emission levels. In the 0.12 mm exhaust variation, emission levels are CO 2.54%, CO2 8.81%, HC 74 ppm, O2 7.10% whereas in the intake variation 0.15 mm, emission levels are CO 4.92%, CO2 5,92%, HC 19 ppm, O2 8,88%. Keywords: Valve Clearance, Performance, Gas Emissions